Uji Biodegradasi Bioplastik Berbahan Dasar Limbah Cair Industri Tahu - Amanda Cornelia Prastiwi; Naniek Ratni Juliardi A. R (Jurnal Serambi Engineering, 2024)
Plastic is the main source of environmental pollution in Indonesia. To mitigate this problem, liquid waste from the tofu industry can be used as a raw material in the production of bioplastics. The research aims to utilise this waste and analyse the effects of additives on the biodegradability of the resulting bioplastics. Bioplastic synthesis is carried out using a variety of additives such as glycerol plasticiser, chitosan, palm oil and gum arabic, followed by biodegradation testing. The results indicate that liquid waste from tofu production has potential as a raw material for bioplastic production, which can be completely degraded within 15 days. Different additives influenced the degradation rate, with higher glycerol concentrations increasing biodegradability. In conclusion, bioplastics from tofu waste could serve as an environmentallyfriendly alternative to reduce plastic waste.